2003
DOI: 10.1038/sj.bmt.1704245
|View full text |Cite
|
Sign up to set email alerts
|

Differences between graft product and donor side effects following bone marrow or stem cell donation

Abstract: Summary:We report graft product stem cell yields and donor safety results of a randomized multicenter study comparing allogeneic peripheral blood stem cell (PBSC) PBSC transplantation with BM transplantation. Matched HLA-identical sibling donors (n ¼ 329) were randomized to filgrastim-mobilized PBSC or bone marrow (BM) donation groups. Median yields per kg recipient weight of CD34 þ cells, T cells, and natural killer (NK) cells, respectively, were approximately two-fold, eight-fold, and greater than eight-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 26 publications
3
65
1
1
Order By: Relevance
“…26 In line with earlier observations, we found a significantly lower CD34 þ cell concentration in the products of female than that in male donors, irrespective of the donor's age (Po0.05). 3,26 In our study, we could not confirm the observation of Suzuya et al 27 who found a negative correlation between donor's age, CD34 mobilization capacity and yield. This can be best explained by the fact that the investigated cohort of donors in our study was older than the donors described by Suzuya et al, 27 with a median age of 41 years (range 11-72), and only two were younger than 18 years.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…26 In line with earlier observations, we found a significantly lower CD34 þ cell concentration in the products of female than that in male donors, irrespective of the donor's age (Po0.05). 3,26 In our study, we could not confirm the observation of Suzuya et al 27 who found a negative correlation between donor's age, CD34 mobilization capacity and yield. This can be best explained by the fact that the investigated cohort of donors in our study was older than the donors described by Suzuya et al, 27 with a median age of 41 years (range 11-72), and only two were younger than 18 years.…”
Section: Discussioncontrasting
confidence: 99%
“…3,26 Beside recipient variables (for example, body weight and required CD34 amount), the concentration of CD34 þ cells in the peripheral blood of donors is predictive for estimation of the number of procedures. 26 In line with earlier observations, we found a significantly lower CD34 þ cell concentration in the products of female than that in male donors, irrespective of the donor's age (Po0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Anecdotal reports have been published describing the development of leukemia after G-CSF-primed PBSC donation. [49][50] However, three small studies of normal adult PBSC donors did not show clinically significant changes in white cell numbers and no donor leukemia was noted. [51][52][53] In a recent analysis, 203 healthy volunteer donors were followed up actively for 5 years after G-CSF-mobilized PBSCs were collected.…”
Section: Donor Safetymentioning
confidence: 99%
“…Smaller studies from related donors suggest that these frequent side effects occur with the same pattern in related donors. [12][13][14][15] Sporadic case reports and a recent large survey among transplant teams demonstrate that the donation procedure can be associated with a small but real risk for serious adverse events and reactions (SAE/R). [16][17][18][19] Current experience suggests that risks seem to be higher for related than for unrelated donors with the caveat of reporting bias and lack of an adequate amount of prospective follow-up data in the related donor setting.…”
Section: Introductionmentioning
confidence: 99%